Critical Discourse Analysis Of Child Marriage Practices In The Yuni’s Movie - Ardiani; Aimie Sulaiman; Citra Asmara Indra (Profesional Muda Cendekia Publishing, 2023)
This research generally strives to see the discourse of the marriage practices of children who are raised in the movie Yuni with the method of researching the critical discourse discharge of the Norman Fairclough known as 3-dimensional analysis is text, scholary practice) (socialche practice) and social practice. According to him there is a kind of dialectic that occurs between social context (macro) and language (micro) itself. Thus, Fairclough tries to combine linguistic traditional and socio-linguistic. According to him, to know the meaning of the text as a whole, not enough if it only sees the linguistic aspects that it is necessary to connect it to the social context. That way, although the film is part of the literary study, this study will not lose its sociological aspect. This study will analyze each scene containing text or discourse of child marriage practices, analyze how the audience interprets the film through the application that has comments and analyzes the social context outside the media affecting the text raised in the movie Yuni. Data collection was done through the analysis which was then captured the screen in the scene containing child marriage text. Not only that, researchers also collect data through library studies and documentation which then the overall data was analyzed using 3-dimensional analysis of Norman Fairclough. From the results of the analysis conducted by the researcher, at least 9 scenes containing discourse of child marriage practices in Yuni's film including themselves that there is still an assumption that education for women is not important, some societies do not know the existence of the law Article 7 Number 16 of 2019, the marriage of children is not equipped with physical, psychic and mature knowledge, the environment plays an important role in directing teenagers, the income of the pigs that encourage the practice of marriage of children, and the school that has not functioning maximally.